AN ANALYSIS OF ILLOCUTIONARY ACTS IN THE HORROR STORYTELLING VIDEO “IMPIAN SATPAM” BY NADIA OMARA: A PRAGMATIC STUDY - Gadis Kamilah Cahyadi; Zahra Maulidia; Aidil Syah Putra (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT Digital storytelling on YouTube has become an increasingly popular form of communication; however, studies investigating illocutionary speech acts in Indonesian horror storytelling remain limited. Previous research has predominantly examined educational, promotional, and podcast discourse, while horror narratives have received comparatively little scholarly attention despite their distinctive communicative characteristics. Therefore, this study aims to identify and analyze the types and communicative functions of illocutionary speech acts employed in Nadia Omara’s YouTube video entitled Impian Satpam. This study adopted a descriptive qualitative design using a pragmatic approach. The data consisted of utterances containing illocutionary speech acts extracted from the selected video uploaded to Nadia Omara’s official YouTube channel. Data were collected through observation and documentation, including repeated viewing, transcription, identification, classification, and interpretation of the utterances. The analysis was conducted based on Searle’s classification of illocutionary speech acts. The findings revealed 35 utterances containing illocutionary speech acts, comprising representative (28.57%), directive (34.29%), commissive (14.29%), and expressive (22.85%) acts, whereas declarative acts were absent. Directive acts emerged as the dominant category, indicating that the storyteller primarily employed language to invite audience participation, provide guidance, and sustain interaction throughout the narrative. These findings demonstrate that illocutionary speech acts function as an essential pragmatic strategy for conveying information, expressing emotions, and enhancing audience engagement, thereby contributing to the effectiveness of contemporary digital storytelling on YouTube. ABSTRAK Digital storytelling di YouTube telah menjadi salah satu bentuk komunikasi yang semakin populer, namun penelitian yang mengkaji realisasi tindak tutur ilokusi dalam narasi horor Indonesia masih terbatas. Sebagian besar penelitian terdahulu berfokus pada wacana pendidikan, promosi, atau podcast, sehingga narasi horor masih relatif kurang mendapat perhatian meskipun memiliki karakteristik komunikasi yang khas. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis jenis serta fungsi komunikatif tindak tutur ilokusi yang digunakan dalam video YouTube Nadia Omara berjudul Impian Satpam. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan pragmatik. Data penelitian berupa tuturan yang mengandung tindak tutur ilokusi yang diperoleh dari video yang diunggah pada kanal YouTube resmi Nadia Omara. Pengumpulan data dilakukan melalui teknik observasi, dokumentasi, transkripsi, identifikasi, klasifikasi, dan interpretasi, sedangkan analisis data didasarkan pada klasifikasi tindak tutur ilokusi menurut Searle. Hasil penelitian mengidentifikasi sebanyak 35 tuturan yang mengandung tindak tutur ilokusi, yang terdiri atas tindak tutur representatif (28,57%), direktif (34,29%), komisif (14,29%), dan ekspresif (22,85%), sedangkan tindak tutur deklaratif tidak ditemukan. Tindak tutur direktif merupakan kategori yang paling dominan, yang menunjukkan bahwa pencerita secara konsisten menggunakan bahasa untuk mengajak, memberikan arahan, dan mempertahankan keterlibatan audiens selama proses penceritaan. Temuan ini menunjukkan bahwa tindak tutur ilokusi merupakan strategi pragmatik yang penting dalam memperkuat interaksi, keterlibatan emosional, dan efektivitas komunikasi dalam digital storytelling kontemporer di YouTube.